Reframing the policy discourse: A comparative analysis of teacher preparation for rural and remote education in Australia, South Africa and Mexico - Ledger, Susan; Masinire, Alfred; Angel Díaz Delgado, Miguel; Burgess, Madeline (Education Policy Analysis Archives, 2021)
The Organisation for Economic Cooperation and Development (OECD) has highlighted a ‘vicious cycle of decline’ in rural, regional and remote (RRR) regions, with significant inequalities in educational outcomes between rural and urban areas. However, interventions have not resulted in transformative or lasting improvements to education in rural contexts. This paper presents a cross-comparative country analysis of current global policy on RRR education. We used a policy analysis framework to interrogate national policy texts concerning teacher education for RRR contexts in three countries - Australia, South Africa and Mexico. A rigorous selection process of the literature yielded 17 key policy texts, which were examined for the influences, practices, language and outcomes relating to teacher education preparation for RRR locales. Findings highlighted a legacy of historical influences and a metrocentric bias in policy texts, with limited examples of assets-based education. We argue that these factors may be perpetuating the significant and persistent disadvantage in RRR education. We recommend an alternative policy discourse that recognises the productivities and potentialities of an assets-based approach within the local context, where school leaders and teachers are positioned as central change agents in RRR education.